2015
DOI: 10.1007/s10549-015-3463-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SDF-1/CXCR4-induced epithelial–mesenchymal transition by kisspeptin-10

Abstract: Recently we have shown that breast cancer cell invasion was dramatically increased when co-cultured with MG63 cells. In addition we have generated mesenchymal transformed MCF-7 breast cancer cells (MCF-7-EMT), showing significantly increased invasion in contrast to wild type MCF-7 cells (MCF-7 WT). In this study we have analyzed whether stromal derived factor-1 (SDF-1) is responsible for MCF-7 and T-47-D breast cancer cell invasion and epithelial-mesenchymal-transition (EMT). In addition we have analyzed wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Although the impact of CAF in metastatic spread has been previously demonstrated [50][51][52][53] , we show here the complementary role of two distinct CAF subpopulations in metastases. We identify a crosstalk between CAF-S1 and cancer cells involving both CXCL12 and TGFβ, consistent with data showing that CAFs secrete CXCL12 and promote cancer cell migration 16,17,[54][55][56][57][58] . In addition, we highlight the role of TGFβ, a well-known EMT inducer 4,59,60 and an important player in fibroblast activation 50,[61][62][63] .…”
Section: Discussionsupporting
confidence: 89%
“…Although the impact of CAF in metastatic spread has been previously demonstrated [50][51][52][53] , we show here the complementary role of two distinct CAF subpopulations in metastases. We identify a crosstalk between CAF-S1 and cancer cells involving both CXCL12 and TGFβ, consistent with data showing that CAFs secrete CXCL12 and promote cancer cell migration 16,17,[54][55][56][57][58] . In addition, we highlight the role of TGFβ, a well-known EMT inducer 4,59,60 and an important player in fibroblast activation 50,[61][62][63] .…”
Section: Discussionsupporting
confidence: 89%
“…showing significantly increased invasion in contrast to wild-type MCF-7 (MCF-7 WT) cells were generated using prolonged mammosphere culture (34,35). Expression of S100A4 mRNA in MCF-7-EMT cells was significantly increased to 165.1±21.0% as compared with MCF-7 WT cells (=100%; P<0.05) ( Fig.…”
Section: Expression Of S100a4 and Effects Of Anti-s100a4 Antibody Trementioning
confidence: 99%
“…In osteosarcoma cells cultured in vitro , the expression of the KISS-1 gene is negatively correlated to the cell proliferation and invasion (6), moreover, after KISS-1 transfection and overexpression, the proliferation and invasion of human osteosarcoma MG-63 and U-2OS cells decline. However, clinical studies have found that the patients with high expression of KISS-1 and GPR54 suffer a higher tumor metastasis rate and mortality (7,8). This study was designed with those findings in mind, we used KISS-1 overexpression vector or siRNA to either highly express or knockdown expression of KISS-1 in the MG-63 osteosarcoma cell line in vitro , in order to analyze the mechanism of proliferation, apoptosis and autophagy of the tumor cells.…”
Section: Introductionmentioning
confidence: 99%